2006
DOI: 10.1188/06.cjon.213-219
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Considerations for Female Adoelscent and Young Adult Patients Following Cancer Therapy: A Guide for Counseling Patients and Their Families

Abstract: During the past 20 years, an increase in survival among pediatric patients with cancer has occurred, and a need exists to be proactive prior to cancer therapy regarding issues related to fertility. Chemotherapy and radiation can cause a number of deleterious side effects to female patients, including early menopause and its associated side effects of osteoporosis and heart disease as well as the inability to carry a pregnancy to term or conceive a child. Many drugs and fields of radiotherapy are associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…Clinical guidelines (Lee et al . ) and researchers (Davis ; Maltaris et al . ) recommend that fertility information should be provided at the point of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical guidelines (Lee et al . ) and researchers (Davis ; Maltaris et al . ) recommend that fertility information should be provided at the point of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Seven journal articles met the search criteria (Crawshaw, Glaser, Hale, & Sloper, 2004;Davis, 2006;Dow & Kuhn, 2004;Goodwin et al, 2007;Keating, 1992;Koeppel, 1995;Wallace, 2007). Medline ® and PsycINFO ® databases were searched for peer-reviewed, English-language articles that included FP discussions by healthcare professionals with patients with cancer.…”
Section: Study Instrumentmentioning
confidence: 99%
“…A lthough advances in treatment have led to increased cancer survival rates, they also have brought certain undesirable consequences, including infertility, which may result as an adverse long-term effect of cancer treatment (Davis, 2006;Rosoff & Katsur, 2003). Cancer treatments involving surgery, chemotherapy, or radiation may damage fertility.…”
mentioning
confidence: 99%
“…Women newly diagnosed with cancer are, of course, overwhelmed and concerned with the issue of survival, but this also is the time when they should be informed that the recommended treatment may damage their fertility (Davis, 2006). The literature has shown that women diagnosed with cancer are highly interested in fertility intervention; however, many oncologists are either not providing the necessary information to these women and their families or are doing so suboptimally (Lee et al, 2006).…”
Section: Etiologymentioning
confidence: 99%